Orbital actinomycotic mycetoma caused by Streptomyces cinnamoneus. Issue 1 (15th June 2015) - Walton, Stuart; Martin, Patricia; Tolson, Carla; Plumridge, Susannah; Barrs, Vanessa R
Case summary: An 18-month-old male neutered Ragdoll cat presented with an 8 week history of progressive unilateral right-sided mucopurulent nasal discharge and exophthalmos. Magnetic resonance imaging revealed a heterogeneous right retrobulbar mass and bilateral nasal cavity disease. Filamentous structures seen on cytology of retrobulbar and nasal biopsies were mistakenly identified as filamentous fungal hyphae. Subsequent investigations revealed that the cat had a retrobulbar actinomycotic mycetoma with invasion of the globe. The aetiological agent was identified on 16S recombinant DNA sequencing as Streptomyces cinnamoneus . After exenteration and chronic antimicrobial therapy the cat was alive and well 3 years after presentation. Relevance and novel information: This is the first report of a pathogenic role of S cinnamoneus in a cat. Orbital actinomycotic mycetomas in cats can resemble mycotic granulomas.